2014
DOI: 10.1088/0004-637x/791/1/28
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-Rich Dust Past the Asymptotic Giant Branch: Aliphatics, Aromatics, and Fullerenes in the Magellanic Clouds

Abstract: Infrared spectra of carbon-rich objects which have evolved off the asymptotic giant branch reveal a range of dust properties, including fullerenes, polycyclic aromatic hydrocarbons (PAHs), aliphatic hydrocarbons, and several unidentified features, including the 21 µm emission feature. To test for the presence of fullerenes, we used the position and width of the feature at 18.7-18.9 µm and examined other features at 17.4 and 6-9 µm. This method adds three new fullerene sources to the known sample, but it also c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
131
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(139 citation statements)
references
References 91 publications
(118 reference statements)
8
131
0
Order By: Relevance
“…But these lower metallicity objects harbour more prominent 11.3 microns features than in the Galaxy (where less than a handful of PNe with SiC are known). This 11.3 microns feature could be due to PAHs emission, but its shape is fully consistent with SiC (Sloan et al(2014)). SiC can indeed be less abundant but a bright SiC feature can be observed if the condensation sequence is different at low Z, leading to grain coating, with SiC forming on top of amorphous carbon grains (Sloan et al(2014); Lagadec et al 2007;Leisenring et al 2008).…”
Section: Dust Evolution After the Agbsupporting
confidence: 67%
See 2 more Smart Citations
“…But these lower metallicity objects harbour more prominent 11.3 microns features than in the Galaxy (where less than a handful of PNe with SiC are known). This 11.3 microns feature could be due to PAHs emission, but its shape is fully consistent with SiC (Sloan et al(2014)). SiC can indeed be less abundant but a bright SiC feature can be observed if the condensation sequence is different at low Z, leading to grain coating, with SiC forming on top of amorphous carbon grains (Sloan et al(2014); Lagadec et al 2007;Leisenring et al 2008).…”
Section: Dust Evolution After the Agbsupporting
confidence: 67%
“…Thus, Cerrigone et al(2011) proposed that it was associated with hydrocarbons. Sloan et al(2014) showed that it was always associated with two unidentified features at 15.8 and 17.1 microns. They showed that these two features were clearly linked to alkynes, confirming that the 21 micron feature is associated with hydrocarbons.…”
Section: Dust Evolution After the Agbmentioning
confidence: 95%
See 1 more Smart Citation
“…Sources with crystalline silicates in the SMC 30788 R. Sahai Sloan et al (2014) Embedded carbon stars and post-AGB objects in the LMC 40159 A. Tielens Kemper et al (2010), Woods et al (2011) Filling colour-colour and colour-mag. space in the LMC 40650 L. W. Looney Gruendl et al (2008) YSOs (and some deeply embedded carbon stars) in the LMC 50167 G. Clayton RSGs in the LMC and SMC 50240 G. C. Sloan…”
Section: Spectramentioning
confidence: 99%
“…The 3.4 µm feature is generally thought to arise from the C-H stretching vibration of aliphatic hydrocarbon materials, while the 3.3 µm feature is due to the C-H stretching mode of aromatic hydrocarbons. Also detected in some UIE sources are the aliphatic C-H deformation bands at 6.85 and 7.25 µm (see Sloan et al 2014, and see Table 3 in Yang et al 2016a for a summary).…”
Section: Introductionmentioning
confidence: 99%